The obstacles to preparing ethical teachers for Arab schools in Israel: The case of one Arab college of education. (3rd April 2022) - Saada, Najwan
ABSTRACT: This multiple case study explores the obstacles to preparing prospective Arab teachers to deal with values/moral issues, from the perspective of Arab teacher educators in one Arab college of teacher education in Israel. In-depth interviews with 13 teacher educators were conducted and analysed. Four obstacles were reported by teacher educators. The first was the scholastic-oriented curriculum in their college and the exclusive focus on developing the student teacher's technical skills, disciplinary knowledge and intellectual capacities. The second was related to the teacher educators' qualifications—their motivation and professional awareness with respect to dealing with values/moral issues in their courses. The third was related to the quality of the student teachers, their desire to become teachers, their commitment and their understanding of the moral work of teaching. The fourth pertained to the college of education's culture and the lack of a systemic policy of preparation for values education.